PENGAJUAN KLAIM DANA PERTANGGUNGAN WAJIB KECELAKAAN LALU LINTAS DALAM PERSPEKTIF KEPASTIAN HUKUM DAN PERLINDUNGAN KORBAN - Muhammad Akbar; Purwanto Purwanto; Febri Noor Hediati (Universitas Labuhanbatu, 2025)
The Mandatory Road Traffic Accident Compensation Fund constitutes a form of social insurance designed to provide legal protection and financial compensation for victims of traffic accidents. This study aims to analyze the claim submission mechanism of the mandatory compensation fund from the perspective of legal certainty and victim protection, as well as to assess its effectiveness in implementation in Balikpapan City. The research employs a socio-legal approach supported by a normative analysis to examine the alignment between legal norms and their practical implementation. Data were collected through field research and an examination of relevant statutory regulations. The findings indicate that, normatively, the claim submission mechanism is supported by a clear legal framework and an adequate institutional structure. However, its effectiveness remains constrained by several factors, particularly the low level of public awareness and legal literacy regarding victims’ rights. This condition affects the optimal realization of legal protection intended for accident victims. Therefore, strengthening legal education, enhancing procedural transparency, and improving inter-agency coordination are necessary to ensure greater legal certainty and more effective victim protection.Keywords: Mandatory Compensation Fund; Legal Certainty; Victim Protection; Traffic Accidents